Life cycle assessment of solar thermal systems - Fernandes, V. (2014)
The better understanding of cost-benefit, economic and environmental performances of solar thermal systems (STSs) is crucial for designers to be able to take a conscious and weighted decision about the installation of these systems. Therefore the goal of this research was to create a methodology for designers to support decision-making in the selection of the most adequate STS for a project and as result to contribute to a more sustainable built environment. This methodology allows the calculation of the potential environmental impacts, such as the global warming potential, acidification, eutrophication, ozone depletion, embodied energy, amongst others, together with the life-cycle costs resulting from the implementation of STSs in buildings. The system boundary includes the production of the various parts of the solar thermal system, such as the solar collector and the hot water tank, the assembly process, the maintenance stage, the auxiliary energy consumption and the end of life of this system. In the economic analysis, both initial and maintenance costs are considered together with the cost of the auxiliary energy. At the end, it is possible to quantify carbon, energy and cost payback periods. One practical application of the methodology will be carried out in the end of this work, aiming the comparison between four different STSs to be applied in a case study. The case study showed that both the energy and environmental payback times of a STS are less than 3 years and the life cycle cost payback period vary from 7 to 13 years.